Integration of the Internet of Things (IoT) in Renewable Energy Management Strategies to Increase the Competitiveness of Machine Companies in the Green Industry Era - Anang Pribadi; Nur Wening (PT. Anagata Sembagi Education, 2025)
The changing business landscape over the past two decades has been marked by the accelerated adoption of digital technology, increasing environmental awareness, and the demand for sustainable business models. In this context, companies are required to not only compete effectively but also transform towards a Green Industry by leveraging renewable energy and Internet of Things (IoT) technology. Traditional management strategies such as SWOT, TOWS, and QSPM remain relevant, but their effectiveness increases significantly when combined with modern approaches such as Blue Ocean Strategy and supported by the use of real-time data from the IoT. The study showed that IoT implementation can improve operational efficiency, reduce machine downtime, strengthen supply chain management, and optimize renewable energy utilization, resulting in reduced carbon emissions and energy cost savings of up to 20%. Quantitative findings demonstrate a significant contribution of the integration of management strategies, IoT, and renewable energy to company performance with an R² value of 0.67, while qualitative interviews confirmed IoT's role as a catalyst for digital-green transformation. However, challenges such as initial investment costs, data security risks, and limited technical skills remain inhibiting factors. This study concludes that the integration of IoT with renewable energy and management strategies is a strategic foundation for increasing competitiveness while strengthening the legitimacy of corporate sustainability in the green industry era.